(untitled) (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The focus of this research discusses the transformation of maqāṣid shari’āh in mediation practices in divorce cases, and the revitalization of adat in mediation practices in Bugis and Mandar communities. This study is a field legal research using historical and socio-anthropological approaches, while the data is analyzed using maqāṣid shari’ah theory and social change theory. Data collection techniques are based on literature studies on legal sources related to the discussion.This study concludes that divorce is an extraordinary case in the religious courts, dynamics of mediation practice in Religious Courts have successful mediation for a written peace agreement in peace deed, other mediation products are partially successful mediation and partially unsuccessful mediation, mediation products are not successful is that husband and wife are committed to divorce; maqāṣid shari‘āh transformation can be a major consideration by judges in mediation practice to save households on the verge of collapse, so that maqāṣid shari‘āh is very urgent to place in Perma No.1 of 2016, and revitalization of Bugis-Mandar customary is an effort to revive the value of life sirondo-rondoi, siamasei, sianuang pa’mai, and sibaliparri, also animate shara’ which is performed petta kalie (Bugis) or puang kali’ (Mandar).